Lymphocytic Choriomeningitis Virus Infection in FVB Mouse Produces Hemorrhagic Disease - Schnell, Frederick J. (Public Library of Science, 2012)
The viral family Arenaviridae includes a number of viruses that can cause hemorrhagic fever in humans. Arenavirus infection often involves multiple organs and can lead to capillary instability, impaired hemostasis, and death. Preclinical testing for development of antiviral or therapeutics is in part hampered due to a lack of an immunologically well-defined rodent model that exhibits similar acute hemorrhagic illness or sequelae compared to the human disease. We have identified the FVB mouse strain, which succumbs to a hemorrhagic fever-like illness when infected with lymphocytic choriomeningitis virus (LCMV). FVB mice infected with LCMV demonstrate high mortality associated with thrombocytopenia, hepatocellular and splenic necrosis, and cutaneous hemorrhage. Investigation of inflammatory mediators revealed increased IFN-γ, IL-6 and IL-17, along with increased chemokine production, at early times after LCMV infection, which suggests that a viral-induced host immune response is the cause of the pathology. Depletion of T cells at time of infection prevented mortality in all treated animals. Antisense-targeted reduction of IL-17 cytokine responsiveness provided significant protection from hemorrhagic pathology. F1 mice derived from FVB×C57BL/6 mating exhibit disease signs and mortality concomitant with the FVB challenged mice, extending this model to more widely available immunological tools. This report offers a novel animal model for arenavirus research and pre-clinical therapeutic testing.